The Impact of Ankle Strategy Training on Improving Dynamic Balance Performance in Individuals - Dian Oktafianti; Dyah Pitaloka (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
The decline in dynamic balance among the elderly is a critical health issue because it substantially increases the risk of falls, injuries, and loss of functional independence, largely due to age-related decreases in muscle strength, coordination, and postural control. This study aimed to examine the effect of ankle strategy exercises on the dynamic balance of elderly individuals, using a pre-experimental one-group pretest–posttest design. A total of 33 elderly participants were selected through purposive sampling, and dynamic balance was measured using the Timed Up and Go Test (TUGT) as an indicator of mobility and fall risk. The results of the Wilcoxon signed-rank test showed a statistically significant improvement in dynamic balance following the intervention (ρ = 0.000 < 0.05), indicating the effectiveness of ankle strategy exercises. Although the absence of a control group and the relatively small sample size limit causal inference and generalizability, these exercises represent a simple, low-cost, and feasible intervention that can be implemented in both institutional and community-based elderly care programs. Future studies are recommended to involve larger samples, include control groups, and conduct long-term follow-up to strengthen evidence for fall prevention and geriatric rehabilitation.